ANALISIS POTENSI DAN STRATEGI PENGEMBANGAN AGROWISATA DI DESA ALEBO KECAMATAN KONDA KABUPATEN KONAWE SELATAN - La Ode Alwi; Abdul Gafaruddin; Munirwan Zani (Halu Oleo University, 2023)
This research aims to know: (1) the Agrotourism Potential in Alebo Village Konda Subdistrict of South Konawe Regency and (2) the Strategy of agro-tourism development in Alebo Village Konda Subdistrict of South Konawe Regency. The types of data are primary and secondary data. at the same time, methods of data analysis used tabulation and descriptive analysis, SWOT, and analysis of Quantitative Strategic Planning Matrix (QSPM). The results of the study indicate that (1) Alebo Village is included in the category of potential to be developed into an agro-tourism area based on eleven criteria such as land use, climate, hydrology, population, cultural arts, Spasial Plan, Regional Industrial Development Master Plan, agricultural attractions, natural attractions, tourism resources availability, access (2) Priority of agro-tourism development strategy from three alternative strategies that can be used priority of agro-tourism development strategy that can be done is to improve the quality of service and quality of tourism facilities with its own characteristics so that consumers are satisfied with the services and facilities that exist.